Statistics of the stress, strain-rate and spin fields in viscoplastic polycrystals. (15th May 2021) - Das, Shuvrangsu; Ponte Castañeda, Pedro
Highlights: Homogenization estimates for the macroscopic response of nonlinear polycrystals. Consistent estimates for the first and second moments of the microscopic fields. Fluctuations of the fields increase with nonlinearity and grain anisotropy. Intragranular fluctuations of the continuum vorticity do not vanish. Continuum spin fluctuations have significant impact on elastic spin fluctuations. Abstract: This paper provides estimates for the stress, strain-rate and spin field statistics in viscoplastic polycrystals. They are obtained by combining the fully optimized second-order (FOSO) homogenization method with the self-consistent estimate for linear polycrystalline aggregates. The FOSO linearization method allows the consistent estimation of the field statistics in nonlinear composites and polycrystals directly from those in suitably optimized linear comparison composites (LCC). For the LCC, a novel generalized approach is used to extract the field statistics of the stress, the strain-rate and also of the continuum-spin fields (including the second moments). Then, the stress-field statistics are used to extract the plastic-spin statistics, which, together with the continuum-spin statistics, provide consistent estimates for the microstructural-spin statistics. Applications to power-law viscoplastic FCC polycrystals and ice-like HCP polycrystals are considered, and the overall and intragranular field fluctuations are computed and found to increase with nonlinearity exponent and grain anisotropy. In particular, the covariance tensors of the continuum-spin fluctuations within the grains of viscoplastic polycrystals, which are characterized here for the first time by means of nonlinear homogenization methods, are found to be quite significant, even when the corresponding averages of the continuum-spin in the grains are negligible, and thus have a strong influence on the corresponding microstructural-spin fluctuations.